2010
DOI: 10.1007/s12177-010-9056-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of contrast sensitivity with LogMAR visual acuity and glycosylated hemoglobin in non-insulin dependent diabetes mellitus

Abstract: A tertiary care center-based prospective case-control study was undertaken to evaluate the association of contrast sensitivity with LogMAR visual acuity and glycosylated hemoglobin (HbA1c) in 205 cases of non-insulin dependent diabetes mellitus and 115 controls. LogMAR visual acuity and contrast sensitivity were scored using ETDRS and Pelli-Robson charts, respectively. Bivariate correlation between contrast sensitivity and LogMAR visual acuity showed significant inverse correlation in cases without retinopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 10 publications
4
32
3
2
Order By: Relevance
“…(6) Misra et al also found association between contrast sensitivity and visually acuity as well as glycosylated haemoglobin in patients with Type 2 Diabetes Mellitus. (7) Our study found that there is some reduction in contrast sensitivity in diabetic patients even before they develop visible retinal changes on ophthalmoscopy. However this reduction is not statistically significant when compared with healthy controls.…”
Section: Contrast Sensitivity In Diabetic Patients Without Retinopathsupporting
confidence: 48%
“…(6) Misra et al also found association between contrast sensitivity and visually acuity as well as glycosylated haemoglobin in patients with Type 2 Diabetes Mellitus. (7) Our study found that there is some reduction in contrast sensitivity in diabetic patients even before they develop visible retinal changes on ophthalmoscopy. However this reduction is not statistically significant when compared with healthy controls.…”
Section: Contrast Sensitivity In Diabetic Patients Without Retinopathsupporting
confidence: 48%
“…Prediabetic hyperinsulinemia and toxic inflammatory factors might affect the ganglion cell layer of the neural retina, resulting in reduced visual functions including contrast sensitivity 22. Results from our study demonstrate that subjects with DN have reduced contrast sensitivity compared with those without DN.…”
Section: Discussionmentioning
confidence: 66%
“…; McAnany & Park ,, ), letter contrast sensitivity (CS) (Stavrou & Wood ; Misra et al. ; McAnany & Park ) and MP sensitivity (Verma et al. ; Nittala et al.…”
Section: Introductionmentioning
confidence: 99%